Оптичні властивості і стабільність двошарових тонких плівок рубрен-alq3, одержаних методом вакуумного напорошення - Gavrilko, T.; Nechytaylo, V.; Viduta, L.; Baran, J. (Publishing house "Academperiodika", 2018)
We report on the optical and structural characterization of the two-component vacuum deposited (VD) rubrene (Rub)-Alq3 films. As is known, Rub-doped OLED active materials demonstrate both promising electroluminescence and transistor characteristics. However, in terms of operational lifetime, the Rub practical application in basic devices has a few draw-backs related to its chemical instability. Our main attention was focused on the role of the Alq3 coverage and the isomeric transformation of a Rub molecule on its chemical stability in these structures. By monitoring the evolution of PL emission in time, we found that the Rub degradation in Rub-Alq3 films is slower than that in vacuum-deposited Rub layers. These results demonstrate that the deposition of an Alq3 layer can be a way to enhance the stability of Rub to the photo-oxidation in optoelectronic devices. The Rub amorphous film crystallization at elevated temperatures in open air was observed for the first time.